PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MEDIA CANVA INTERAKTIF DI SEKOLAH MENENGAH PERTAMA NEGERI 8 KOTA JAMBI - Abhil Putra Darenli; Jamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of students in Islamic Religious Education (PAI) at Class VII D of SMP Negeri 8 Jambi City, as indicated by the low percentage of students achieving the minimum mastery criteria. The purpose of this study was to improve students' learning outcomes through the use of interactive Canva media in the learning process. This research employed the Classroom Action Research (CAR) method, which was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The subjects of this study were 27 students of Class VII D at SMP Negeri 8 Jambi City. Data were collected through observation, tests, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The results showed that the use of interactive Canva media significantly improved students’ learning outcomes. In the pre-cycle stage, the learning mastery percentage was only 37%, with 10 students achieving mastery. After the implementation of interactive Canva media in Cycle I, the mastery percentage increased to 66%, with 18 students achieving mastery. In Cycle II, the mastery percentage further increased to 89%, with 24 students achieving mastery, exceeding the predetermined success indicators. In addition to improving learning outcomes, the use of interactive Canva media also enhanced students’ learning activities, motivation, attention, and participation during the learning process. Therefore, interactive Canva media proved to be effective in improving students’ learning outcomes in Islamic Religious Education for Class VII D students at SMP Negeri 8 Jambi City.